Increased temperature and CO2 alleviate photoinhibition in Desmarestia anceps from transcriptomics to carbon utilization - Iñiguez, Concepción (Journal of experimental botany, 2017)
© The Author 2017. Published by Oxford University Press on behalf of the Society for Experimental Biology.